2017
DOI: 10.18488/journal.1007/2017.7.9/1007.9.238.250
|View full text |Cite
|
Sign up to set email alerts
|

Financial market anomalies: evidence from Tunisia stock market

Abstract: Keywords:Week of the year effect, Day of the week effect, Week of the month effect, Month of the year effect, Stock return index (TUNINDEX) ABSTRACTThe aim of this study is to investigate the presence of seasonal market anomalies (calendar anomalies) and to analyze their effects on the behavior of financial investors in terms of decisions and profit on the Tunisian market during the entire period that starts on January 2003 and ends on 31 December 2015. This work examines four calendar effects which are the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In emerging markets, for example, in the Indian stock market Gupta (2017) studied the January effect using 15 years worth of data and found no anomalous evidence. In the Tunisian stock market Ahmed & Boutheina (2017) also did not find evidence of the January effect but confirmed the month of the effect in August and April. Balaban et al (1995) found evidence of the January effect in the Turkish stock market.…”
Section: Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…In emerging markets, for example, in the Indian stock market Gupta (2017) studied the January effect using 15 years worth of data and found no anomalous evidence. In the Tunisian stock market Ahmed & Boutheina (2017) also did not find evidence of the January effect but confirmed the month of the effect in August and April. Balaban et al (1995) found evidence of the January effect in the Turkish stock market.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Although questions around the evolution of the January effect specifically are not new, Perez (2018), Gupta (2017) and Patel (2016) continue to investigate the evolution of the January effect in advanced and emerging markets. Others such as Ahmed & Boutheina (2017) and Gupta (2017) focused on the evolution of other monthly anomalies such as the December effect and the Mark Twain effect.…”
Section: Introductionmentioning
confidence: 99%
“…This is as these effects are less prominent than the January effect. Referring to higher than average returns in October as compared to other months, both Ahmed & Boutheina (2017), Balaban et al (1995), and Floros (2008) did not find evidence of the Mark Twain effect in the Tunisian, Istanbul and Greek stock markets, respectively. Furthermore, Rossi & Gunardi (2018) did not find any significant evidence of the Mark Twain effect and December effect in Germany, France, Italy and Spain.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Although questions around the evolution of the January effect specifically are not new, Perez (2018), Gupta (2017) and Patel (2016) continue to investigate the evolution of the January effect in advanced and emerging markets. Others such as Ahmed & Boutheina (2017) and Gupta (2017) focused on the evolution of other monthly anomalies such as the December effect and the Mark Twain effect. This paper seeks to add to the existing monthly anomalies literature by using data from which covers the entire US stock market history and to confirm the US results by comparing with similar markets.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a minor positive impact on Karachi markets in the holy month of Ramadan and the prices have been less volatile during this period (Khan et al , 2017). The October returns for the Tunisian market have been low compared to other months of the year and negatively significant (Ahmed and Boutheina, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%